Electrochemotherapy with Calcium Chloride and 17β-Estradiol Modulated Viability and Apoptosis Pathway in Human Ovarian Cancer - Zofia Łapińska; Michał Dębiński; Anna Szewczyk; Anna Choromańska; Julita Kulbacka; Jolanta Saczko (MDPI AG, 2020)
Estrogens (Es) play a significant role in the carcinogenesis and progression of ovarian malignancies. Depending on the concentration, Es may have a protective or toxic effect on cells. Moreover, they can directly or indirectly affect the activity of membrane ion channels. In the presented study, we investigated in vitro the effectiveness of the ovarian cancer cells (MDAH-2774) pre-incubation with 17β-estradiol (E2; 10 µM) in the conventional chemotherapy (CT) and electrochemotherapy (ECT) with cisplatin or calcium chloride. We used three different protocols of electroporation including microseconds (µsEP) and nanoseconds (nsEP) range. The cytotoxic effect of the applied treatment was examined by the MTT assay. We used fluorescent staining and holotomographic imaging to observe morphological changes. The immunocytochemical staining evaluated the expression of the caspase-12. The electroporation process's effectiveness was analyzed by a flow cytometer using the Yo-Pro™-1 dye absorption assay. We found that pre-incubation of ovarian cancer cells with 17β-estradiol may effectively enhance the chemo- and electrochemotherapy with cisplatin and calcium chloride. At the same time, estradiol reduced the effectiveness of electroporation, which may indicate that the mechanism of increasing the effectiveness of ECT by E2 is not related to the change of cell membrane permeability.